Hodgkin lymphoma after disseminated Mycobacterium genavense infection, Germany - Trauth, Janina; Discher, Thomas; Fritzenwanker, Moritz; Imirzalioglu, Can; Arnold, Tobias; Steiner, Dagmar; Richter, Elvira; Crisponi, Laura; Grimbacher, Bodo; Herold, Susanne (Emerging infectious diseases, 2022)
Mycobacterium genavense infection, a rare nontuberculous mycobacteria infection, occurs in heavily immunocompromised patients (i.e., those with advanced HIV disease, genetic disorders, or acquired immunologic disorders and those undergoing immunosuppressive therapy). We report a case of disseminated M. genavense infection preceding Hodgkin lymphoma in a patient without obvious risk factors for this infection.